Cardiovascular Sequelae of Bronchopulmonary Dysplasia in Preterm Neonates Born before 32 Weeks of Gestational Age: Impact of Associated Pulmonary and Systemic Hypertension - Pramod Pharande; Arvind Sehgal; Samuel Menahem (Journal of Cardiovascular Development and Disease, 2024)
Bronchopulmonary dysplasia (BPD) remains the most common respiratory disorder of prematurity for infants born before 32 weeks of gestational age (GA). Early and prolonged exposure to chronic hypoxia and inflammation induces pulmonary hypertension (PH) with the characteristic features of a reduced number and increased muscularisation of the pulmonary arteries resulting in an increase in the pulmonary vascular resistance (PVR) and a fall in their compliance. BPD and BPD-associated pulmonary hypertension (BPD-PH) together with systemic hypertension (sHTN) are chronic cardiopulmonary disorders which result in an increased mortality and long-term problems for these infants. Previous studies have predominantly focused on the pulmonary circulation (right ventricle and its function) and developing management strategies accordingly for BPD-PH. However, recent work has drawn attention to the importance of the left-sided cardiac function and its impact on BPD in a subset of infants arising from a unique pathophysiology termed postcapillary PH. BPD infants may have a mechanistic link arising from chronic inflammation, cytokines, oxidative stress, catecholamines, and renin–angiotensin system activation along with systemic arterial stiffness, all of which contribute to the development of BPD-sHTN. The focus for the treatment of BPD-PH has been improvement of the right heart function through pulmonary vasodilators. BPD-sHTN and a subset of postcapillary PH may benefit from afterload reducing agents such as angiotensin converting enzyme inhibitors. Preterm infants with BPD-PH are at risk of later cardiac and respiratory morbidities as young adults. This paper reviews the current knowledge of the pathophysiology, diagnosis, and treatment of BPD-PH and BPD-sHTN. Current knowledge gaps and emerging new therapies will also be discussed.